Childhood overweight and obesity in Europe: Changes from 2007 to 2017 - Buoncristiano, Marta; Spinelli, Angela; Williams, Julianne; Nardone, Paola; Rito, Ana Isabel; García-Solano, Marta; Grøholt, Else Karin; Gutiérrez-González, Enrique; Klepp, Knut Inge; Starc, Gregor; Petrauskienė, Aušra; Kunešová, Marie; et al. (Obesity reviews, 2021)
The Childhood Obesity Surveillance Initiative (COSI) routinely measures height and weight of primary school children aged 6-9 years and calculates overweight and obesity prevalence within the World Health Organization (WHO) European Region using a standard methodology. This study examines the trends in the prevalence of overweight and obesity from the first round of COSI carried out in 2007/2008 to the latest of 2015/2017 in 11 European countries in which data were collected for at least three rounds. In total 303,155 children were measured. In general, the prevalence of overweight and obesity among boys and girls decreased in countries with high prevalence (Southern Europe) and remained stable or slightly increased in Northern European and Eastern European countries included in the analysis. Among boys, the highest decrease in overweight (including obesity) was observed in Portugal (from 40.5% in 2007/2008 to 28.4 in 2015/2017) and in Greece for obesity (from 30.5% in 2009/2010 to 21.7% in 2015/2017). Lithuania recorded the strongest increase in the proportion of boys with overweight (from 24.8% to 28.5%) and obesity (from 9.4% to 12.2%). The trends were similar for boys and girls in most countries. Several countries in Europe have successfully implemented policies and interventions to counteract the increase of overweight and obesity, but there is still much to be done.
Keywords: obezita dětí a dospívajících; Europe; Female; Overweight; Prevalence; dítě; ženské pohlaví; overweight; temporal trend; lidé; Evropa; školy; Schools; prevalence; Male; children; index tělesné hmotnosti; nadváha; Child; mužské pohlaví; Body Mass Index; obesity; Pediatric Obesity; Humans